Need to Intervene: An Exploratory Study of Nurses’ Experiences With Patienthood - Marian A. O. Cohen PhD; Jim McQuaid PhD; Ruth Remington PhD, RN (Journal of Patient Experience, 2021)
Much has been written about the patient experience, but there is little information about experiences of providers as patients. Since lay patients and providers have differing perspectives and expectations, it is important to identify those elements shared by those in each group and those that diverge. This study identified experiences of nurses as being a patient or a family caregiver of a patient as well as identified assessments of the healthcare system by nurses. An exploratory study using a self-administered electronic questionnaire with a group of registered nurses was conducted. Assessments of the system by responders were positive when addressing quality of care, interactions among healthcare personnel, and interactions with patients. However, when discussing their experiences as patient, nurses reported they encountered problems with coordination of care, responses of medical personnel, attention to details of care, and responses to their attempts to become more involved. Results confirm issues raised by patients who are not medical experts in patient satisfaction studies. Adding a professional perspective highlights where problems with the healthcare system lie.